Radiation Monitoring and Dose Estimation of the Fukushima Nuclear Accident - Takahashi, Sentaro (Springer Japan : Imprint: Springer, 2014)
This book provides comprehensive research findings related to the environmental monitoring of radiation, levels of radioactive nuclides in various environments, and dose estimation in residents after the Fukushima nuclear power plant accident caused severe environmental contamination with radioactive nuclides. At the beginning of the book, a technical review written by a leading researcher of nuclear reactor technology explains what happened at the power plant. The review is followed by a commentary from a former member of the International Commission on Radiological Protection, providing the reader with easily understandable information about the concept of radiation dosage. In the main part of the book, a series of scientific reports presents valuable data on the radiation surveys of the environment, environmental radioactivity, transfer models and parameters of radioactive nuclides, and dose assessment among residents. These reports present a wide range of findings from the research carried out in a variety of activities by large governmental organizations as well as by small private groups and individuals. The reader thus will find a large collection of valuable and interesting data related to the environmental contamination by radioactive nuclides after the Fukushima accident. Although earlier reports on this issue have been made public, this book is the only publication to fully depict the actual situation by providing comprehensive data obtained by diverse organizations and individuals.